Gerakan Pendidikan Islam Kontemporer Bagi Anak Berkebutuhan Khusus di SLB Negeri 2 Mataram - Sari, Eva Sofia; Hotimah, Husnul (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The development of an increasingly complex era, education as the main door that must be implemented by applying time so that education can make humans become plenary first in developing education oriented in the context of Islamic values. The essence of Islamic education is an alternative source for the needs of the world of education, because Islamic education is an effort or process of guiding changes in attitudes and behavior of students in accordance with the instructions of Islamic teachings or in accordance with the new life, namely the Qur'an. The focus of this research tries to examine several concepts as basic assumptions in research, namely, first, examining the concept of Islamic education, second, the nature and objectives of Islamic education, third, the dynamics of the Islamic education movement, especially in the development of children with special needs in special needs students in SLB Negeri 2 Mataram. the source of the values of Islamic teachings. The approach approach is (Library research) literature studies to find theoretical concepts about work ethic and relevance to Islamic education, then supported by various references, articles, journals, books and so on. Specifically, it can be denied that the Islamic education movement can provide teaching efforts on aspects of developing intellectual, nurturing, planned in preparing students to know, understand, live up to faith, caution, and have a noble character in practicing Islamic teachings.